Facilitating the co-construction of interculturality in teletandem through pedagogical mediation - Schaefer, Rodrigo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Telecollaboration relates to the use of online technologies in the context of language teaching and learning (O’Dowd, 2013). This study aimed at discussing how pedagogical mediation can contribute to the coconstruction of interculturality in teletandem, the specifi c “mode of telecollaboration” (Telles, 2015a:604) in my research. Data analysis showed that opportunities for at least initial steps of a decentering attitude (Liddicoat & Scarino, 2013) came about due to pedagogical mediation, which means that teacher-mediators can encourage discussions that go beyond superfi cial cultural representations in the teletandem context.